User Satisfaction Evaluation of ShopeePay: A Technology Acceptance Model (TAM) Approach in Analyzing Digital Wallet Service Acceptance - Ridho Afriano (Information Technology and Systems, 2025)
This study aims to evaluate ShopeePay user satisfaction by using the Technology Acceptance Model (TAM) approach to analyze the factors that influence the acceptance of digital wallet services. Specifically, this study assesses the impact of Perceived Usefulness (PU), Perceived Ease of Use (PEOU), and Attitude Toward Using (ATU) on Behavioral Intention (BI) as well as user satisfaction in carrying out transactions through ShopeePay. The research method uses a quantitative approach by distributing questionnaires to active ShopeePay users, and data analysis is conducted using validity tests, reliability tests, multiple linear regression, and Structural Equation Modeling (SEM) to examine the relationships between variables in the model. The research results show that PU and PEOU have a significant effect on ATU and BI, while BI has been proven to be the main predictor of ShopeePay user satisfaction. These findings indicate that perceptions of ease of use and usefulness are crucial aspects in the acceptance of digital wallet services among young users. This study has several limitations, including the scope of respondents being limited to certain regions, so the results cannot yet be generalized nationally, as well as the use of basic TAM variables that do not include external factors such as security risks or application promotions. The novelty of this research lies in the integration of the TAM model to directly link behavioral intention with user satisfaction, which has not been widely studied in the context of the ShopeePay digital wallet in Indonesia. In addition, this study provides empirical contributions in mapping the psychological factors that influence the continued use of e-wallet services in the digital era